Efficient Cooperative MAC and Routing in Wireless Networks - Jacob, Lillykutty; Shamna, H.R. (Discoveries in Agriculture and Food Sciences, 2015)
Cooperative communication refers to the collaborative processing and retransmission of the overheard information at those stations surrounding the source. It exhibits various forms at different protocol layers and introduces many opportunities for cross layer design and optimization. To fully reap the benefits of cooperative communications in wireless networks, the entire protocol stack - physical, MAC, and routing protocols - should be carefully redesigned or reengineered. In this paper, we first propose a cooperative MAC protocol by enhancing IEEE 802.11 DCF with minimal modifications to maximize the benefit of cooperative diversity. Its performance is compared to that of an existing cooperative MAC and legacy 802.11 DCF protocols and shown to be superior. We also propose a cluster based cooperative routing protocol which has minimal control overhead and time consumed in establishing the cooperative paths. Through extensive simulations, the performance of the proposed protocols are evaluated and compared to other combinations of MAC and routing protocols.